2008
DOI: 10.1177/0363546508320572
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tunnel-Graft Length on the Biomechanics of Anterior Cruciate Ligament-Reconstructed Knees

Abstract: Various clinical scenarios exist in which the length of available graft that could be pulled into the bone tunnel (femoral or tibial) could be in question. To address this concern, this study showed that reducing the tendon graft length in the femoral bone tunnel from 25 mm to 15 mm did not have adverse affects in a goat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 33 publications
2
106
1
2
Order By: Relevance
“…However, Zantop et al showed that the outcome of the ACL reconstruction in goats at 12 weeks was not significantly different from 6 weeks. 43 This supports the conclusion that the outcome with respect to AP laxity and ligament stiffness is not worse or better than the ACL reconstruction in the goat.…”
Section: Discussionsupporting
confidence: 82%
“…However, Zantop et al showed that the outcome of the ACL reconstruction in goats at 12 weeks was not significantly different from 6 weeks. 43 This supports the conclusion that the outcome with respect to AP laxity and ligament stiffness is not worse or better than the ACL reconstruction in the goat.…”
Section: Discussionsupporting
confidence: 82%
“…The difference in height between the graft groups might also in part explain the difference in graft diameter [22]. However there are reports suggesting that a shorter graft length inside the tunnels does not lead to lower pull-out strength or more frequent graft incorporation complications [23]. Graft length inside the tunnels might therefore be of less importance than previously thought.…”
Section: Discussionmentioning
confidence: 97%
“…Also, according to Zantop et al, 11 tendon-bone anchoring occurs only in the first 12 mm of the bone tunnel, and a short graft length (15 mm) does not have a negative correlation with knee kinematics and structural properties. Logan et al, 12 however, suggested that the dimension of the graft may be important because it ultimately determines the surface area of tendon-bone healing.…”
Section: Discussionmentioning
confidence: 95%